Qualitative Studies in Quality of Life: Methodology and Practice - Tonon, Graciela (Springer, 2015)
This volume explores the use and relevance of qualitative methods for the study of quality of life. It analyzes the role of qualitative researcher and the role of the context and the culture in quality of life studies. It presents the use of qualitative methods in real projects carried out in specific fields: geography, health, community studies, labor life and yoga. Finally, the book proposes the use of mixed methods that are considered as the third methodological approach in social research.